Is the help helpful? : how to create online help that meets your users' needs - Weber, Jean Hollis (Hentzenwerke Pub., 2004)
Is the Help Helpful? presents the full cycle of help content development, regardless of the operating system running the application, the type of help being produced, or the tools used to produce it. In this book, you'll discover the 10 most common complaints that users have with online help, the causes of the underlying problems, and ways to avoid those problems, the 11 steps in the ideal help development process, their benefits, and the problems that arise when a step is left out, techniques for planning, writing, editing, reviewing, and testing online help and sample plans and specifications for your help project. Other books teach how to use a particular online help authoring tool, but they don't teach how to plan, write, edit, and test the help system being developed. Is the Help Helpful? supplements tool-specific instructions by presenting the basics of help content development, regardless of the operating system running the application, the type of help being produced, or the tools used to produce it. It is intended for technical writing students, project managers, writers, editors, and others involved in the production of online help.